GE_GERICHTE P/9276/2023 vom 18. März 2024 - GE Cour de justice (2024)
CALCUL DU DÉLAI;SOUPÇON;REMISE À LA POSTE;BOÎTE AUX LETTRES;TÉMOIN;PREUVE;FAUX INTELLECTUEL DANS LES TITRES | CPP.90; CPP.310; CPP.396